2018
DOI: 10.3390/nano9010042
|View full text |Cite
|
Sign up to set email alerts
|

First Generation Amperometric Biosensing of Galactose with Xerogel-Carbon Nanotube Layer-By-Layer Assemblies

Abstract: A first-generation amperometric galactose biosensor has been systematically developed utilizing layer-by-layer (LbL) construction of xerogels, polymers, and carbon nanotubes toward a greater fundamental understanding of sensor design with these materials and the potential development of a more efficient galactosemia diagnostic tool for clinical application. The effect of several parameters (xerogel silane precursor, buffer pH, enzyme concentration, drying time and the inclusion of a polyurethane (PU) outer lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Nanoparticles have been considered as valuable means in medicinal discipline by the reason of their high surface area to volume ratio and consequence versatility [ 34 , 35 ]. Indeed, nanoparticle-based biomaterials can interact with several biomolecules [ 36 ], resulting in being employed to several biomedical areas—e.g., drug delivery, tissue engineering, and dentistry [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have been considered as valuable means in medicinal discipline by the reason of their high surface area to volume ratio and consequence versatility [ 34 , 35 ]. Indeed, nanoparticle-based biomaterials can interact with several biomolecules [ 36 ], resulting in being employed to several biomedical areas—e.g., drug delivery, tissue engineering, and dentistry [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar successful transition to wire electrodes was achieved for LbL-constructed galactose biosensor that was recently reported at macroelectrodes [22]. Accurate galactose measurements in newborns can predict the presence of the disorder galactosemia [23].…”
Section: Resultsmentioning
confidence: 79%
“…Each of the layers had been previously characterized and studied for their properties, including entire reports on electrochemically-deposited polymer films and work establishing that the xerogel porosity was controllable based on moisture content, aging time, and silane precursor. Moreover, specific combinations of this type of layering were previously investigated and optimized for the detection of target analytes at the macroelectrode surfaces, including successful glucose [3], uric acid [12] and galactose [22] biosensors. In those studies, it was shown that each layer serves a specific and functional purpose, whether enhancing sensitivity, improving selectivity against interferents, or preventing enzyme leakage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations